Model Pelatihan Blended Learning Meningkatkan Hasil Belajar Perawat Tentang Kamar Bedah Dasar - Pancaningsih Pancaningsih (Jurnal Keperawatan, 2021)
The world is having the same problem, Covid-19, it is signed by morbidity and mortality caused by Covid-19. The need of learning process should be done by paying attention onon effectivity and efficiency to reach the optimal result. The blended Learning method become the solution for answering the need of learning process, especially for the nurse. This learning process combines Online and ofline learning so the need of learning can be fulfilled without disregard our government program in decreasing the new cases of Covid 19.This research goals is to identifiy the Blended learning training effectivity to increase the result of the learning proses basic operating room. The research design is using pre experimentusung one group Pre Test and Post Test.The research sample is 50 nurses in basic operating room in Dinas Kesehatan DKI Jakarta by using Total sampling Technique. The research is done in August - September 2021 at Pusat pelatihan Central Java. The Training program is done for 4 days equal as 40 JPL (Online and Ofline).The Research Instrument is using Knowledge Questionaire developed by HIPKABI Jakarta. The Data analysis is useing N Gain Score. The rrsearch result showed quite effective in increasing the result of learning process about basic operating room with the N gain score = 71,812%. The Learning Method became a consideration in The research process. We hope the lack in accessing internet can be minimized. The advantage that we can get is cost eficiency and time and also the result of optimum learning process.